PENGARUH WARNA RUANGAN TERHADAP KECEMASAN PASIEN SAAT PELAYANAN DI KLINIK GIGI - Rhama Pradipta Nabil Saputra; Ida Rahmawati; Emilda Sari (Poltekkes Kemenkes Banjarmasin, 2021)
One of the problems faced for coloring a health facility, such as the practice room and its instruments, is because the practice room and its instruments have specificity in human services. Those who are served are human beings who need care, service, and healing, both physically and mentally. Such human beings certainly have a special emotional temperament. Therefore, the use of color in this case aims to